Mass gathering medicine: 2014 Hajj and Umra preparation as a leading example - Jaffar A. Al‐Tawfiq; Ziad A. Memish (2014)
The importation of infectious diseases during a mass gathering may result in outbreaks. Infectious diseases associated with mass gatherings vary depending on the type and location of the mass gathering. The annual Hajj to Makkah in Saudi Arabia is one of the largest annual religious mass gatherings in the world. Preparation for the Hajj encompasses multiple sectors to develop comprehensive plans. These plans include risk assessment, utilizing existing medical infrastructure, developing electronic and paper-based surveillance activity, and the use of information technology. In this review, we describe key features of the preparedness for the 2014 Hajj and Umra, review the recent impact of emerging viruses such as Ebola in West Africa and the Middle East respiratory syndrome coronavirus (MERS-CoV) in affected countries, and highlight the updated requirements and the required vaccines.